OPTIMALISASI DESAIN INTERIOR PERMANENT MAGNETSYNCHRONOUS MOTOR UNTUK MENGURANGI RIAK TORSI MELALUI PENDEKATAN SIMULASI - Auditya Farha (2023)
Electric motors are electromechanical machines that are widely used in various fields such as industry and automotive. Interior permanent magnet synchronous motor is one type of synchronous type electric motor with a permanent magnet which is often used in electric vehicle. However, one of the characteristics of electric motors with permanent magnets is the presence of torque ripple which gives problems when the motor is operating. This research was conducted to optimize the torsional ripples that exist in the existing design. Optimization is applied to the existing design with an initial condition of torque ripple of 42.58%. Optimization is done by modifying the parameters of the air gap, magnet angle, magnet thickness and slot opening. The optimization process was carried out through software simulation with finite element method using the taguchi method to reduce number experiments from 625 to 25 trials. Through analysis of mean and analysis of variance, the optimization process produces a reduction in torque ripple of 9.71% and increased 0.14% of efficiency. The optimized IPMSM design has torque ripple and efficiency of 32.87% and 96.97% respectively at a motor operating speed of 13500 rpm. In addition, the nominal torque value decreased by 13.9 Nm.